2015
DOI: 10.1017/s0022215114003296
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea syndrome does not negatively affect oral and dental health

Abstract: Obstructive sleep apnoea syndrome does not negatively affect oral and dental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…15 Dry mouth can also occur during treatment of patients with OSA using continuous positive airway pressure devices. 16 Tsuda et al reported that 40% of adults on continuous positive airway pressure for OSA have poor oral health.…”
Section: Introductionmentioning
confidence: 99%
“…15 Dry mouth can also occur during treatment of patients with OSA using continuous positive airway pressure devices. 16 Tsuda et al reported that 40% of adults on continuous positive airway pressure for OSA have poor oral health.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al 24) reported that poor . Sleep deprivation leads to extreme fatigue, stress, and poor oral health behavior, leading to poor oral hygiene, which can cause periodontitis 25) . Hong 26) concluded that the risk of periodontitis is 1.37 times higher in the group with less than six hours of sleep per day, whereas 27) reported that those who slept less than seven hours per day have a higher risk of periodontitis, compared with those who slept seven hours or more per day.…”
Section: Discussionmentioning
confidence: 99%
“…For masticatory function, the variable was dichotomized into two categories: sufficient (≥5 units) vs. insufficient (<5 units) masticatory efficiency depending on the number of functional (occluding) premolar and molar units. The threshold of 5 masticatory units was chosen based on the WHO recommendations indicating that the retention of a minimum of 20 teeth is sufficient for adequate masticatory efficiency and ability [23].…”
Section: Discussionmentioning
confidence: 99%
“…As known, mouth breathing is highly common in patients with OSA, both adults and children, and it may adversely affect oral health [27][28][29][30]. Chronic mouth breathing per se may lead to dryness of the oral cavity and the pharynx, impair the self-cleaning ability of the oral cavity during sleep, and facilitate oral bacterial colonization [23,28]. In this perspective, mouth breathing associated with OSA may be the mediating factor that predisposes to the development of gingivitis and periodontitis [8].…”
Section: Discussionmentioning
confidence: 99%